Impact of predation on the bacterial community structure of Mediterranean mussels during depuration - Blaiotta, Giuseppe; Ciliberti, Ivan; Aponte, Maria; Romano, Raffaele (Frontiers in Microbiology, 2025)
The Mediterranean mussel (Mytilus galloprovincialis) is the most valuable shellfish farmed and consumed in the Western Mediterranean. Like any other filter-feeding organism, mussels are exposed to a wide range of microorganisms. Before consumption, bivalves are subject to depuration to purge the gastrointestinal content, thus minimizing the risk of pathogens’ circulation. Over time, this strategy revealed several shortcomings, most notably concerning Vibrio spp. In this study, the potential use of autochthonous predatory bacteria as a biocontrol strategy to mitigate Vibrio spp. overgrowth in mussels during depuration was evaluated. Moreover, a polyphasic approach based on conventional and culture-independent strategies was used to assess the impact of predation and of depuration on the mussel microbiome during controlled depuration studies. The depuration greatly impacted the bivalve microbiota, jeopardizing its innate resilience. Moreover, the addition of a bacterial predator strain to mussels resulted in the disturbance of the microbiome. Therefore, even though the biotechnological application of bacterial predation in this context may appear promising when monitored by culture-dependent methods, the effect on the mollusks’ microbiome does not seem to be easily predictable, above all when mussels are subject to depuration after the harvest.